A new species of Liolaemus (Iguania: Liolaemidae) from the hot deserts of northern Patagonia, Argentina - Abdala, Cristian S.; Chafrat, Pablo Anselmo; Chaparro, Juan C.; Procheret, Iván Ezequiel; Valdes, Julián; Lannutti, Vanina; Perez, Laura; Quinteros, Sebastián (European Journal of Taxonomy, 2023)
A new species of Liolaemus is described from southwest of the town of Añelo, Neuquén Province, Argentina. Integrative evidence methodology of external morphological characters and molecular phylogenetic analyses of mitochondrial DNA (cyt-b) is used to place the new species to the species group of Liolaemus boulengeri. The new species is phenotypically close to L. mapuche. The new Liolaemus is medium to large in size (males 77.64–83.98 mm, females 72.88–78.58 mm), with evident sexual dichromatism. Genetic distances of the mtDNA (cyt-b) between the new species and its closest relative species are greater than 3% (L. cuyanus 7.48–12.02%; L. josei 7.56–9.60%; L. puelche 8.23–9.93%; L. mapuche 8.51–9.79%). Molecular and morphological phylogenetic results show L. mapuche as the sister species of the new one. The new species is larger than L. mapuche. Dorsal and ventral scales are more numerous in the new species than in L. mapuche, precloacal pores in females are present in L. mapuche and absent in the new species. It has strict psammophilic habits, using sand mounds and sheltering, under Alpataco (Neltuma alpataco) bushes. The L. boulengeri group now contains 75 species distributed in Argentina, Bolivia, Brazil, Chile, Paraguay, Peru and Uruguay.